Continuous flood risk reduction on MSMEs: Implementation of MACTOR program - Muzakar Isa; Liana Mangifera (Economic Journal of Emerging Markets, 2019)
This study aimed at analyzing the vulnerability of an area to flood, identifying the involved stakeholders in the existing institutions, analyzing the significance level and the role of stakeholders in reducing flood risk, and analyzing the relationship among stakeholders in the effort of reducing flood risk in Klaten Regency, Central Java, Indonesia. The data analysis is conducted using indexing, stakeholder analysis based on the MACTOR (Matrix of Alliances and Conflicts: Tactics, Objectives, and Recommendations) program. Findings/Originality: It finds that the vulnerability of the study site is moderate. It also finds some stakeholders that have crucial roles in reducing the flood risk. Their interests can be divided into income, environment, local development and safety. In an effort of reducing the flood risks, Regional Disaster Management Agency along with respective village leaders and volunteers have the central role, while universities have the lowest contribution.